2019
DOI: 10.1590/1809-4392201804331
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antimalarial activity of the volatile oil of Cyperus articulatus (Cyperaceae)

Abstract: Malaria is a disease of global tropical distribution, being endemic in more than 90 countries and responsible for about 212 million cases worldwide in 2016. To date, the strategies used to eradicate this disease have been ineffective, without specific preventive measures such as vaccines. Currently, the existing therapeutic arsenal is limited and has become ineffective against the expansion of artemisinin-resistant Plasmodium, demonstrating the need for studies that would allow the development of new compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
4
6
0
Order By: Relevance
“…The main chemical constituents present in this EO sample were muskatone, cyclocolorenone, α-pinene, pogostol, α-copaene and caryophyllene oxide. The compositional results obtained are in accordance with the previously published EO of C. articulatus rhizome collected in the state of Pará, Brazil [5,22]. On the other hand, the same species, when collected in African countries (e.g., Egypt), presented different main compositions, including γ-patchoulene, caryophyllene oxide and α-cadinol [23], indicating a high variability in the composition of EO.…”
Section: Discussionsupporting
confidence: 89%
“…The main chemical constituents present in this EO sample were muskatone, cyclocolorenone, α-pinene, pogostol, α-copaene and caryophyllene oxide. The compositional results obtained are in accordance with the previously published EO of C. articulatus rhizome collected in the state of Pará, Brazil [5,22]. On the other hand, the same species, when collected in African countries (e.g., Egypt), presented different main compositions, including γ-patchoulene, caryophyllene oxide and α-cadinol [23], indicating a high variability in the composition of EO.…”
Section: Discussionsupporting
confidence: 89%
“…The hydroalcoholic extract of Jucá did not present cytotoxic activity in the cell viability assay with MTT and had a hemolysis of <9% at a maximum concentration of 2000 µg/mL, with 0% hemolysis at concentrations below 31.25 µg/mL. Similar results were obtained for C. articulatus essential oil, which showed a noncytotoxic effect for human lung fibroblasts [52].…”
Section: Discussionsupporting
confidence: 75%
“…Working with a different Amazonian plant, Assis et al [33] obtained an IC 50 value of 1.21 µg/mL for the P. falciparum W2 strain using a Cyperus articulatus residue extract. In another study on the same plant (C. articulatus) but using the essential oil, a similar IC 50 was obtained [52]. This may indicate an unraveled potential that Amazon biodiversity poses to the discovery of new antiplasmodial compounds.…”
Section: Discussionsupporting
confidence: 63%
“…65,66 The same approach was found from a recent study that reported the Cyperus articulatus essential oil has anti-malarial (Plasmodium falciparum) due to the compounds; mustakone, cyclocolorenone, cyperotundone, α-cyperone, α,βunsaturated carbonyl moiety. 67 This is likely to be due to the antimalarial potential of these compounds which may be related to the tendency of the nucleic acids of Plasmodium to react with the α,βunsaturated carbonyl moiety. 68 With regard to volatile oil, the components of the oil extracted from Opuntia ficus indica were identified as follows, unsaturated fatty acids, triacylglycerols, phytosterols, and tocopherols.…”
Section: Figure 3: Chemical Structures Of Some Betalainsmentioning
confidence: 99%